BİYOGRAFİ ÇALIŞMALARI İÇİN ÖNEMLİ BİR KAYNAK"EMEKLİ SANDIGI ARŞİVİ" - Çog, Mehmet (Fırat University, 2004)
In this study, it is discuss that arehiv of office retirement by value Biography studies relation to Ottoman State in 19nt century end age. The matter in documents, acquainted about officials civil and army whose works 1914-1927 at Ottoman State a public sector. Especially, vhen about anybody is'nt find nothing it get basic information as birtday, deathday, family, duty and birthplace. This search discussioned that how is benefit from arehiv of office retirement and disployed concret döcüments.
Keywords: Religious Studies; Din Araştırmaları